Safety based on the behavior and accident rate of the collaborators of a mining company - Cabanillas Coba, Agripina (2022)
Work events or accidents that result in injuries and fatalities occur daily in mining companies; According to studies carried out, the most frequent root cause of work accidents is due to substandard attitudes, in this way the requirement to carry out an investigation with the application based on Behavior-Based Safety (SBC) for the analysis and improvement of the behavior is recognized. behavior of the collaborator, the objective of this study was to establish the influence of the SBC and the tendency of accidents of the collaborators to focus and work more on the behavior of the collaborator, since it is this that helps the anticipation, recognition, evaluation and control of those factors originating or coming from substandard acts of work, which can cause accidents, deterioration of health, well-being, discomfort and inefficiency. From the investigations carried out, a 90% decrease in accident rates is shown based on the application of the SBC, and a great relationship is determined in the Safety variables based on the behavior and accident rate of the collaborators.